EXPERIMENTAL VALIDATION OF PSIDIUM GUAJAVA AND MADHUCA INDICA EXTRACTS AND FRACTIONS FOR PARKINSON’S DISEASE IN MICE - Mudita Mishra; Seema Tomar; Ashutosh Mishra (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Parkinsonism is a neurodegenerative disease, mainly imbalance in dopamine neurotransmitter in mid brain, which manifestation of dysfunctions of extra pyramidal like akinesia, tremor, rigidity and catalepsy etc., even cognitive and memory loss. The current study is framed to evaluate the effect of Psidium guajava and Madhuca indica extract and fraction in Rotenone (RTN) induced Parkinson disease (PD) in mice. Further ,in vivo anti-PD activity has been evaluated by Rotarod, actophotometer, and chimney test to assess extrapyramidal, cognitive and memory function. Later, changes in biomarker level such as reduced glutathione (GSH), malondialdehyde (MDA), superoxide dismutase (SOD), catalase (CAT), and dopamine level in the whole brain were measured. Finally, histopathology of cerebrum area was examined at 40x magnification to access restoring integrity and maintaining the architecture of neuronal cell in the treatment group compared to control group and L-DOPA as a standard treatment group.The Rotarod, Actophotometer, and chimney test demonstrated that rotenone group administration declines performance time, decreases locomotion, cognitive and memory respectively. The treatment of Psidium guajava and Madhuca indica extracts and fractions(200, and 400 mg/kg p.o. and 50, 100mg/kgs significantly (p < 0.05 to p < 0.0001) reversed whole brain reduced glutathione (GSH), malondialdehyde (MDA), superoxide dismutase (SOD), catalase (CAT), and dopamine level altered and significant pathological changes occur. The current study provides validation of Psidium guajava and Madhuca indica extracts and fractions for its anti-PD activity and could be a valuable source for the treatment of PD in future.